Vaccination and medication against Bovine respiratory disease complex (BRDC) - Kurćubić Vladimir; Ilić Zoran; Đoković Radojica; Petrović Milan P.; Caro-Petrović Violeta (Biotechnology in Animal Husbandry, 2018)
BRDC causes pneumonia of cattle, due to which high morbidity and mortality, decreasing food intake and daily growth, and quality of carcasses is significantly reduced. Preventive application of cattle vaccination and treatment of diseased animals with therapeutic agents, with the aforementioned losses, leads to the fact that BRDC is the most expensive cattle disease worldwide. Given the complex etiology (the influence of more viral and bacterial agents), it is characteristic that if viral agents cause disease, the morbidity level is high and the mortality rate is lower. Cattle affected by bacterial infections have a sporadic morbidity and a higher mortality rate. There are a number of predisposing factors originating from the environment or hosts that have a negative impact on the health status of cattle. So, there are a number of challenges that must be solved in the future, with the aim of developing new technologies that would contribute to increasing animal resistance, eliminating risk factors and reducing exposure to pathogens.